Matic motorcycle transmission damage detection system using internet of things-based expert system - Suhadi Suhadi; Muhamad Nur; Sulistyowati Sulistyowati; Amat Suroso (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The development of the motorcycle industry in Indonesia has developed quite significantly from year to year, the BPS (Central Statistics Agency) noted that in 2019 the number of motorcycle sales reached 106.657.952 units, and the AISI (Indonesian Motorcycle Industry Association) in 2020 the type of scooter (matic) of 2,696,557 units or 87.9%, this automatic type of motorbike is the largest contributor to two-wheeled vehicles and is the favorite type of vehicle for Indonesians. Automatic transmission or what is known as CVT (Continuous Variable Transmission), which is an automatic speed transfer system according to engine speed using a V-belt. In previous research, the use of IoT (Internet of Things) is used as an automatic air quality monitoring control system, air quality conditions can be seen quickly and accurately from the monitor. The goal of this study is to use a vibration sensor and the CBR (Case Based Reasoning) method to solve damage to matic motor components. The results of this study are (a) the case average value is 0,76, (b) the CVT component parameter is 80% the average value is 0,94, (c) the CVT component weight parameter is from 60% the average value is 1,26.